2002
DOI: 10.1002/app.10125
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and dynamic mechanical properties of rice husk ash–filled natural rubber compounds

Abstract: A laboratory-sized two-roll mill was used to incorporate rice husk ash into natural rubber (NR). A conventional vulcanization system was used for curing and cure studies were carried out on a Monsanto rheometer. Physical testing of the NR vulcanizates involved determining tensile and tear resistances and hardness. Swelling behavior of NR compounds and scanning electron microscopy were used to investigate the interaction between rice husk ash and natural rubber. Also, dynamical mechanical thermal analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…For filled rubbers, the modulus depends on filler content, crosslink density, filler-filler and filler-rubber interactions that affect the segmental mobility of the rubber chains. The modulus normally increases with increasing amount of filler [39] or degree of filler-rubber interaction [40]. The silica-filled NR with TESPT has the highest storage modulus, indicative Figure 9.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 98%
“…For filled rubbers, the modulus depends on filler content, crosslink density, filler-filler and filler-rubber interactions that affect the segmental mobility of the rubber chains. The modulus normally increases with increasing amount of filler [39] or degree of filler-rubber interaction [40]. The silica-filled NR with TESPT has the highest storage modulus, indicative Figure 9.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 98%
“…It was observed that the dynamic mechanical properties of NR vulcanisates were considerably improved by the addition of lignin. The mechanical and dynamic mechanical properties of rice husk ash-filled NR compounds were studied by Da Costa et al 20 The T g values of filled rubber vulcanisates shifted to higher temperatures, showing the presence of crosslinks, which restrict the mobility of polymer chains. The interactions between fillers and rubber phase also account for the higher properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have been studying the use of RHA as filler in natural and/or synthetic rubber [81]- [83], [101], [102]. Overall results indicate that RHA can be used as a cheap filler for natural rubber materials where high quality mechanical properties are not required.…”
Section: Rha /Elastomers Compositesmentioning
confidence: 99%